Remarks on Oriental species of Allophrys Förster described by A. Reshchikov (Hymenoptera: Ichneumonidae: Tersilochinae) - Khalaim, Andrey I.; Belokobylskij, Sergey A. (Zootaxa, 2017)
Two species of the genus Allophrys Förster were recently described from Oriental region by A. Reshchikov with co-authors (Yue et al. 2017). According to its original description and photographs, A. falcatus Reshchikov from the Philippines actually is a distinct member of the family Braconidae, and we transfer this species preliminarily to the genus Microctonus Wesmael (comb. nov.) of the subfamily Euphorinae. Another species, A. cantonensis Reshchikov & Yue from South China, was described on basis of a single male, and its further identification is expected to be problematic until its female discovered and described.